The red minaret: Memoirs of Ibrahim Ghusheh (ex-spokesman of Hamas). By Ibrahim Ghusheh. Beirut: Al-Zaytouna Centre for Studies and Consultations, 2013, pp. 288, ISBN: 978-9953-572-24-6 - Hossain, Ishtiaq (IIUM Press, 2014)
The Red Minaret: Memoirs of Ibrahim Ghushehis the autobiography of Ibrahim Ghusheh, the official spokesman of Hamas during 1991-1999. Originally written in Arabic, the work was translated into English by Hassan Ibrahim and Salma al-Houry.